Making impression for distorted flabby anterior lower ridge a comparative study (Mustansiria Dental Journal, 2005)
Confusion may exist in facing the problem of impressions for hypermobilemucosa specially when the problem is how to make this impression, various techniqueshave been advocated and the proper selection of one technique or another depends onavailable knowledge of functional and histologic anatomy for the development ofimpression procedure with a wide difference in the interpretation of the denturefoundation. impression pressures have been thought to be a primary cause of tissuedisplacement and consequently a factor of denture instability. This study was carried outto compare 2 different impression techniques for anterior ilabby lower ridge, it has beenconcluded that more retention with better patient satisfaction were gained with lowerdentures made using the window impression technique